Epidemiological research of violence against children in families in Serbia - Hanak Nataša; Tenjović Lazar; Išpanović-Radojković Veronika; Vlajković Ana; Beara Mirjana (Temida, 2013)
In the paper the results of an epidemiological study conducted in 2010-2011 as a part of the regional project Balkan Epidemiological Study on Child Abuse and Neglect (BECAN) are presented. The goal of the research was to estimate the prevalence of physical, psychological and sexual violence against children in the family as well as prevalence of feeling of neglect in children. Gender and age differences in the prevalence of violence, as well as differences with respect to geographic region and urbanicity of place of the children’s’ residence were also examined. The stratified cluster sample consisted of 4027 children attending the fifth and seventh grades of the primary school and the second grade of the high school. Data was collected by an adapted version of the questionnaire ICAST-C (ISPCAN Child Abuse Screening Tool-Chidren Version - ICAST-C). At least one experience of psychological violence in the lifetime was reported by 68,4% of children, whereas at least one experience of physical violence was reported by 69,2% of children. Feeling of neglect was experienced by 28.8% of children at least once in their lifetime. At least one experience of sexual violence was reported by 8.5% children, whereas 3,7% of them reported the experience of contact sexual violence in the past year. The results indicate that girls are more exposed to psychological violence and report more feeling of neglect. Conversely, boys report more exposure to sexual violence. The rate of severe forms of physical, psychological and sexual violence is about 0.5 to 1%. [Projekat je realizovan kroz Sedmi okvirni program Evropske Komisije(FP7), pod oznakom HEALTH-F2-2009-223478]